Legal Consequences of Medical Accidents and Medical Malpractice in Indonesia - Muhammad Ghozali; Cut Afra; Deddi Agusriadi; Sudirman Suti (International Journal of Law, Social Science, and Humanities, 2024)
Medical malpractice, which refers to errors or negligence committed by doctors and medical personnel when treating patients. This malpractice can have serious consequences, such as worsening the patient's health condition or even causing death. This act of malpractice has legal consequences, and therefore, it is important to have a clear legal system in the health sector. The research conducted is of a normative juridical nature, using various approaches to understand this problem. The results of the study indicate that the criminal law governing medical malpractice is contained in the Criminal Code, which includes elements of negligence. To increase legal certainty for patients who are harmed, there are special laws, namely Law No. 36 of 2009 concerning Health and Law No. 36 of 2014 concerning Health Workers, which regulate law enforcement related to malpractice. Overall, this text emphasizes the importance of legal protection for patients and the responsibility of doctors in medical practice.